KONTRIBUSI KEMAMPUAN AWAL DAN AKTIFITAS BELAJAR SISWA TERHADAP HASIL BELAJAR PADA MATA DIKLAT SISTEM OPERASI JARINGAN DI SMKN 8 PADANG - Arie Findi Pratama; Denny Kurniadi; Titi Sriwahyuni (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This research started from the fact that the result of the learning was low . This fact can be seen from data of the first daily test students in class XI TKJ at academic year 2013/2014. In class XI TKJ 1, there are only 14 people (46%) of students who completed the study, and the students who have not completed was 16 people(53%), then  the students of class XI TKJ 2 the result of students who completed is 12 people (41%), and students who have not completed was 17 people (59%). Factors thought to influence the result of the learning is prior knowledge and student learning activities. Therefore, this study aims to determine the contribution of prior knowledge and learning activities for learning result. This research is correlational. Techniques of data collection using questionnaires classes and documentation. The data were analyzed using statistical methods to correlation and regression. Results of data analysis showed: 1) Prior Knowledge give 53,8 %, contribution to the results of the test, 2), Learning Activities give 23.5 %, contribution to the results of the test 3) Prior Knowledge and learning activities together gives 63,25 % to the results of tests on subjects in class XI TKJ at SMKN 8 Padang. Kata Kunci : Kontribusi, Kemampuan Awal, Aktivitas Belajar, Hasil Belajar, Mata Diklat Sistem Operasi Jaringan, Korelasional, Kuesioner, Pre-test.